2001
DOI: 10.1051/0004-6361:20000411
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of C stars with core/mantle grains: Amorphous carbon + SiC

Abstract: Abstract.A set of 45 dust envelopes of carbon stars has been modeled. Among them, 34 were selected according to their dust envelope class (as suggested by Sloan et al. 1998) and 11 are extreme carbon stars. The models were performed using a code that describes the radiative transfer in dust envelopes considering core/mantle grains composed by an α-SiC core and an amorphous carbon (A.C.) mantle. In addition, we have also computed models with a code that considers two kinds of grains -α-SiC and A.C. -simultaneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
4
18
1
Order By: Relevance
“…The inner radius of the dust shell is close to 5 R (see Table 5) as determined by Lorenz-Martins et al (2001). The optical constants of AmC from Rouleau & Martin (1991) and SiC from Pégourié (1988), together with the fractional abundance of SiC/AmC of 0.08 found by Lorenz-Martins et al (2001), are also in good agreement with the values found in this work. These last two characteristics allow us to determine the opacities of SiC used to interpret the spectro-interferometric data of R Scl with the help of the dynamic model (see Sect.…”
Section: Determination Of the Sic Dust Parameterssupporting
confidence: 88%
See 1 more Smart Citation
“…The inner radius of the dust shell is close to 5 R (see Table 5) as determined by Lorenz-Martins et al (2001). The optical constants of AmC from Rouleau & Martin (1991) and SiC from Pégourié (1988), together with the fractional abundance of SiC/AmC of 0.08 found by Lorenz-Martins et al (2001), are also in good agreement with the values found in this work. These last two characteristics allow us to determine the opacities of SiC used to interpret the spectro-interferometric data of R Scl with the help of the dynamic model (see Sect.…”
Section: Determination Of the Sic Dust Parameterssupporting
confidence: 88%
“…The AmC dust grain optical constants from Rouleau & Martin (1991) are the same as adopted for the hydrodynamic calculation (Andersen et al 2003;Höfner et al 2003). Good agreement is also found with the works of Dehaes et al (2007) and Lorenz-Martins et al (2001), who determined a visual optical depth of 0.5 +0.2 −0.3 and a 1.0 μm optical depth of 0.1, respectively. The dust shell inner boundary temperature of 1000 +300 −200 K found by Dehaes et al (2007) agrees well with the value determined in this work.…”
Section: Determination Of the Sic Dust Parameterssupporting
confidence: 78%
“…Sopka et al 1985;Groenewegen 1997;Blanco et al 1998;Lorenz-Martins et al 2001;Gautschy-Loidl et al 2004), our models follow a steeper density distribution ( ∝r −2.3 for AFGL 5379 and CW Leo, ∝r −2.5 for AFGL 3068) (see the density power index "n" in Table 3). …”
Section: Density Distributionmentioning
confidence: 52%
“…The main dust species detected in carbon-rich stars are amorphous carbon, silicon carbide and magnesium sulfide (Treffers & Cohen 1974;Goebel & Moseley 1985;Martin & Rogers 1987;Andersen et al 1999;Chan & Kwok 1990;Hony et al 2002;Zijlstra et al 2006;Lagadec et al 2007;Leisenring et al 2008). One of the key questions in the carbon-species formation is the importance of mantle chemistry, for example the nucleation of amorphous carbon and magnesium sulfides as mantles around silicon carbide grains have been proposed as important dust formation mechanisms (Lorenz-Martins et al 2001;Zhukovska & Gail 2008).…”
Section: Dust Formation In Agb Starsmentioning
confidence: 99%